Effects of Delayed Urinalysis on Urine Leukocytes Counts - Savitri, Sheila; Ariningrum, Dian; Murti, Bhisma (Nexus Biomedika, 2016)
Introduction: Urinalysis is an effective and comprehensive urine examination method. Delayed urine examination may affect the urinalysis results, which in turn may have consequences on a patientâs diagnosis and treatment. This study focuses on the effects of delayed urinalysis on the urine leukocyte counts in patients with urinary tract infection. Methods: This study used a cross sectional design. The research took place at the Clinical Pathology Laboratory of RSUD Dr. Moewardi Hospital in Surakarta, in November 2015. The consecutive sampling method was used to collect 30 urine samples as for analysis. The dependent variable of this study was the urine leukocyte count at 0, 120 and 180 minutes, while the independent variable was the gap time of urinalysis. Urine sample collected from the respondents was divided into three different containers with the same amount of urine and the container was marked (0â, 120â, 180â). The urinalysis was performed according to the order of the mark on each container. This study used Sysmex UX 2000 to count the amount of urine leukocyte. The data, then, were analyzed by the Friedman test. Result: The result showed that there was no significant difference in urine leukocytes counts in delayed urinalysis, shown by the statistical calculations using the Friedman test which obtained a p value of 0.122. Urine samples were collected from 17 female respondents (57%) and 13 male respondents (43%). The age of the respondents ranged from 1 to 78 years old. The average pH of the urine samples was 6.2 with an average specific gravity of 1.012. Conclusions: There is no significant difference in urine leukocyte counts in delayed urinalysis up to 180 minute. Keywords: Delayed Urinalysis, Urine Leukocytes, Sysmex UX 2000